Distribution Channel Analysis At Pt Alamsari Kedelai Agro Sumedang - Hidayanti, Kartika; Hamid, Abdul; Puspasari, Rd. Dewi (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
This study aims to examine the implementation of distribution channels, the challenges faced, and the efforts made to overcome these challenges at PT Alamsari Kedelai Agro Sumedang. The research uses a qualitative method involving observation, interviews, documentation, and triangulation techniques. The study focuses on four main considerations: product, market, company, and environment. Data analysis is descriptive, supported by relevant theories, and emphasizes both the process and information related to the research object. The sampling technique used is purposive sampling, with eight informants.The results show that the company applies a direct distribution channel for the local industrial market, utilizing its own fleet, a zoned delivery system, and cash-based sales. Distribution is concentrated in Sumedang, with expansion into other areas of West Java. The products offered are high-quality imported soybeans with brands tailored to consumer needs. Although prices are not always lower than competitors', consumers continue to choose the product due to its consistent quality.Initial capital challenges were resolved through sound financial management and responsive leadership. The company is also able to adjust prices in response to economic fluctuations, supported by adequate distribution facilities. Despite being relatively effective, the distribution system still faces obstacles such as delivery delays and price competition. Continuous improvement is necessary to maintain customer satisfaction